Tverečiaus šnektos slavizmai prieš 60 metų ir dabar - Zinkevičius, Zigmas (Baltistica, 1986)
Slavic borrowings in the dialect of Tverečius 60 years ago and nowadaysA study on the use of Slavisms in the dialect of Tverečius as recorded by J. Otrębski 60 years ago has been made by E. Gudelytė, a student of Vilnius University under the supervision of the author of the present article. The results of the study are given in the present article. As it turned out, all the representatives of the said dialect now use only 44.3 % of the total number of Slavisms recorded by J. Otrębski. 31 % of the Slavisms are known to and used by the speakers of the older generation (i. e. by people over 35). Besides, 1.7 % of the Slavisms can only be found in certain phrases (phraseological word-combinations) used by the speakers of the older generation. 9 % of the Slavisms occur only in the speech of people over 60. 12.8 % are not used even by the old people, though they have heard and understand them. 1.2 % of the Slavisms have never been heard even by the old people.
Keywords: skoliniai; Tverečiaus šnekta; slavizmai